EKSPERIMEN PERBANDINGAN PENGGUNAAN GULA PUTIH DAN BROWN SUGAR DALAM PEMBUATAN SIRUP LEMON DENGAN METODE CHEONG - Zahra , Alivia Putri; Ilham, wahyudi; Dailami; Alhamdi, Rezki (JURNAL MENATA, 2024)
Fast food and beverages are very popular among customers today because they are quickly made and consumed, so other, healthier alternatives are being sought. By combining fruits or vegetables with the same amount of sugar and leaving them on for a few days to three months, the Cheong method can be used to make any type of syrup. Cheong generally uses white sugar, but some recipes use other options. This study aims to examine the comparison of the use of white sugar and palm sugar to make lemon syrup using the Cheong method. This research method uses an experimental quantitative approach, where the research summarizes two stages of syrup making, namely the stage of making lemon syrup with white sugar, then the stage of making lemon syrup with brown sugar, both of which have a ratio of fruit and sugar with a ratio of 1:1. This study uses an organoleptic test as an assessment of the results of the selected panelists. The use of sugar in in making lemon syrup with the Cheong method can produce insignificant differences in the characteristics of lemon syrup in texture, color, aroma, and taste